THE INFLUENCE OF AGE FACTORS AND THE LEVEL OF LANGUAGE COMPETENCE ON THE PROCESS OF LEARNING FOREIGN LANGUAGES - Akramova Mohinur Akramovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This  article  examines  the  role  of  age  and  language  proficiency  in  foreign language teaching. It demonstrates that a differentiated approach based on students' age and level improves language acquisition and learning motivation. The findings support the  advisability  of  adapting  teaching  methods  and  content  to  foster  sustainable communicative competence.